Technique used by killer whales (Orcinus orca) when hunting for dolphins in Patagonia, Argentina - Coscarella, Mariano Alberto (2015)
Fil: Coscarella, Mariano Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina. Universidad Nacional de la Patagonia; Argentina